What's Happened to the Rate of Return to Business Masters?. Issue 1 (14th May 2015) - Corliss, Michael; Lewis, Phil; Daly, Anne
Abstract : While business masters degrees are popular with students wishing to enhance their career prospects, there is little evidence available on the private rate of return to these degrees in Australia. Furthermore, there is little evidence about the effects of the huge growth in graduates in recent decades and changing business conditions on the profitability of a business masters degree from an individual's point of view. This is despite the expectation that there would be significant consequences of the changes in demand and supply to the relative income of higher degree holders. This paper presents estimates of the rate of return in Australia associated with the completion of business masters degrees over the period 2001 and 2011. The results show that for the average person, there are incentives to complete these degrees, and the private rate of return compares favourably with the real long term real bond rate. However, the profitability of an investment in a business masters has fallen significantly over time.